2010
DOI: 10.3748/wjg.v16.i27.3437
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization with a fine-powder formulation of cisplatin for hepatocellular carcinoma

Abstract: We conclude that TACE using a suspension of DDPH in LPD could be a useful treatment for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…When comparing cisplatin and doxorubicin, the objective early response rates were 50% and 24%, the median progression-free survival time was 8.6 and 3.0 months, and the overall survival rates at 1 and 2 years were 81.0% and 76.0%, and 68.0% and 46.0%, respectively. 24 The response rates of cisplatin and epirubicin were 62.5% and 51.5%, and the overall survival rates at 1 and 2 years were 88.5% and 71.8%, and 83.0% and 57.9%, respectively. 21,26 According to these studies, cisplatin showed a significantly higher response rate, better progression-free survival and better overall survival than the anthracycline agents.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…When comparing cisplatin and doxorubicin, the objective early response rates were 50% and 24%, the median progression-free survival time was 8.6 and 3.0 months, and the overall survival rates at 1 and 2 years were 81.0% and 76.0%, and 68.0% and 46.0%, respectively. 24 The response rates of cisplatin and epirubicin were 62.5% and 51.5%, and the overall survival rates at 1 and 2 years were 88.5% and 71.8%, and 83.0% and 57.9%, respectively. 21,26 According to these studies, cisplatin showed a significantly higher response rate, better progression-free survival and better overall survival than the anthracycline agents.…”
Section: Discussionmentioning
confidence: 91%
“…Twelve articles (two systematic reviews, seven retrospective studies, one historical cohort study, one prospective study and one randomized phase II trial) compared the response rates and survival between cisplatin or miriplatin and other drugs. When comparing cisplatin and doxorubicin, the objective early response rates were 50% and 24%, the median progression‐free survival time was 8.6 and 3.0 months, and the overall survival rates at 1 and 2 years were 81.0% and 76.0%, and 68.0% and 46.0%, respectively . The response rates of cisplatin and epirubicin were 62.5% and 51.5%, and the overall survival rates at 1 and 2 years were 88.5% and 71.8%, and 83.0% and 57.9%, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, suspensions show a longer anticancer drug release time at the tumor border and higher continuous drug concentrations. The longer tissue drug activity period associated with the use of suspensions produces superior antitumor effects, as evaluated by the growth ratio and the results of histopathological investigations [16, 17, 23, 24]. Some problems exist, however.…”
Section: The Comparative Efficacy Of Anticancer Agent-iodized Oil mentioning
confidence: 99%
“…TACE is primarily per- formed as chemolipiodolization, using anticancer drugs mixed with lipiodol [8,9]. There have been several retrospective reports of TACE with anthracyclines versus platinum compounds, suggesting the usefulness of platinum compounds [10,11] [15]. Disease had advanced after previous TACE with epirubicin in 59% of patients.…”
Section: Treatment Strategy and Problems With Tacementioning
confidence: 99%